2010
DOI: 10.3168/jds.2009-2551
|View full text |Cite
|
Sign up to set email alerts
|

Association between uterine disease and indicators of neutrophil and systemic energy status in lactating Holstein cows

Abstract: The objective of this study was to evaluate the association between uterine disease and indicators of neutrophil (PMN) and systemic energy status in dairy cows. Peripheral blood (120 mL) was collected weekly from 84 Holstein cows for PMN isolation and plasma collection from calving until 42 d in milk (DIM). The final analysis included 80 cows. Of those, 20 cows were classified as having metritis (fetid uterine discharge and fever), 15 as having subclinical endometritis (SCE; >or=10% PMN on uterine cytology), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
141
3
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(173 citation statements)
references
References 45 publications
22
141
3
7
Order By: Relevance
“…Glucose is stored as glycogen within the PMN. Concentrations of glycogen in PMN decrease in a manner that is similar to the decrease in blood glucose postpartum with a lag period of~7 days (Galvão et al, 2010). The lag in the decrease in PMN glycogen may represent the time required for glycogen loading during maturation of PMN.…”
Section: Lucy Butler and Garverickmentioning
confidence: 88%
See 1 more Smart Citation
“…Glucose is stored as glycogen within the PMN. Concentrations of glycogen in PMN decrease in a manner that is similar to the decrease in blood glucose postpartum with a lag period of~7 days (Galvão et al, 2010). The lag in the decrease in PMN glycogen may represent the time required for glycogen loading during maturation of PMN.…”
Section: Lucy Butler and Garverickmentioning
confidence: 88%
“…The lag in the decrease in PMN glycogen may represent the time required for glycogen loading during maturation of PMN. Galvão et al (2010) observed that cows developing uterine disease had lesser concentrations of glycogen in their PMN. Their conclusion was that lesser glycogen reserve led to a reduced capacity for oxidative burst in PMN and uterine disease.…”
Section: Lucy Butler and Garverickmentioning
confidence: 90%
“…Negative balances of energy or metabolizable protein may be a major contributing factor (Ingvartsen and Moyes, 2013). Galvão et al (2010a) found that glycogen content of neutrophils (reserve of glucose, the main fuel for neutrophil functions) was lower in early postpartum cows, and was associated with decreased functions of those cells. An inadequate supply of metabolizable protein has been related to impaired function of the immune system (Houdijk et al, 2001).…”
Section: Transition Nutritional Management In Tmr-fed Herdsmentioning
confidence: 99%
“…Metritis and endometritis are frequently observed due to dystocia. Cows that develop uterine disease experience a reduction in neutrophil function such as chemotaxis, phagocytosis, and killing ability around calving (Galvao et al 2010). This may result in increasing the rate of udder infections due to immune suppression.…”
Section: Discussionmentioning
confidence: 99%